The mechanism of public-private partnership in education of the Republic of Belarus (on the example of the pilot project «Construction of preschool institutions in regions of the Minsk region») - Tuleika, Katsiaryna V. (Journal of the Belarusian State University. Economics, 2019)
In this article is offered and reasonable the mechanism of public-private partnership in education of Republic of Belarus on the example of the infrastructure project. The structure of the mechanism public-private partnership is characterized and also featured and revealed interrelations of it elements. The scientific problem of the research consists in permission of a contradiction between objective need of formation and development of public-private partnership for modern social and economic conditions and insufficient degree of its scientific readiness, in particular, after adoption of the special legislation. Research objective is disclosure and scientific justification of the mechanism of public-private partnership in education of Republic of Belarus on the example of the pilot project «Construction of preschool institutions in regions of the Minsk region». Object of a research is education of Republic of Belarus which development is carried out within public-private partnership. The scientific novelty of a research consists in definition of the concept «mechanism of public-private partnership» and justification of his contents in national education of Republic of Belarus. The research assumes use of an integrated approach to formation and use of the mechanism of PPP in the sphere of the domestic education based on interrelation of legal, financial, administrative, technological and social aspects of his realization.
Keywords: public private partnership; educational infrastructure; mechanism of public-private partnership